1968
DOI: 10.1113/jphysiol.1968.sp008452
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tetrodotoxin on the slowly adapting stretch receptor neurone of lobster

Abstract: 1. A study has been made of the effects of tetrodotoxin on the impulse activity, resting membrane potential, input resistance, and the generator potential and its after‐hyperpolarization of the slowly adapting stretch receptor neurone of the lobster. 2. Tetrodotoxin was able to abolish completely within about 2 min the impulse activity in most cells, when given in a dose of 2 × 10−8 g/ml., but in all cells, when administered in a dose of 4 × 10−8 g/ml. After blockage by the toxin in concentrations as high as 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1969
1969
1991
1991

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…When the slow potential deflects to negative at the sensory terminal in reference to the proximal portion of the axon, it may be considered a generator potential. The behavior of the slow potential that was not significantly influenced by tetrodotoxin and procaine is similar to the response of spindle potentials in the frog muscle spindle (ALBUQUERQUE et al, 1969) and in the crustacean slowly adapting stretch receptor neuron (ALBUQUERQUE and GRAMPP, 1968 ;LOWENSTEIN et al, 1963) to application of the drugs. However, the slow potential may not be a generator potential for the following reasons.…”
Section: Discussionmentioning
confidence: 60%
“…When the slow potential deflects to negative at the sensory terminal in reference to the proximal portion of the axon, it may be considered a generator potential. The behavior of the slow potential that was not significantly influenced by tetrodotoxin and procaine is similar to the response of spindle potentials in the frog muscle spindle (ALBUQUERQUE et al, 1969) and in the crustacean slowly adapting stretch receptor neuron (ALBUQUERQUE and GRAMPP, 1968 ;LOWENSTEIN et al, 1963) to application of the drugs. However, the slow potential may not be a generator potential for the following reasons.…”
Section: Discussionmentioning
confidence: 60%
“…Spikes were also eventually suppressed leaving only a small rebound (B3). TTX did not evoke the hyperpolarization reported in the lobster stretch receptor, an effect which was identified with an increased K + permeability as well as a reduced Na + conductance (Albuquerque and Grampp 1968), because the K + current was blocked by TEA in our experiments.…”
Section: Effect Of Ttxmentioning
confidence: 88%
“…The slow potential was not blocked by tetrodotoxin which blocks the initiation of the spike potential. In other mechanosensitive structures such as the muscle spindle, the stretch receptor and the Pacinian corpuscle, tetrodotoxin blocks nerve conduction without depressing appreciably the receptor potential (Ito, 1971;Albuquerque & Grampp, 1968), if the concentration of the drug is not high (Nishi & Sato, 1966). S.MATSUURA 54 GENERATOR POTENTIAL OF BARORECEPTOR FIBRES 55 Results obtained in this study show that the slow potential recorded from a point close to the sensory terminals of the baroreceptor fibres has the typical characteristics of a generator potential, as reported for other mechanoreceptors. In the baroreceptor, the sensory terminals of the fibre have been proposed to be the receptor site from electron microscopic studies, and afferent synapses have not been found around the terminal region (Rees, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…In other mechanosensitive structures such as the muscle spindle, the stretch receptor and the Pacinian corpuscle, tetrodotoxin blocks nerve conduction without depressing appreciably the receptor potential (Ito, 1971;Albuquerque & Grampp, 1968), if the concentration of the drug is not high (Nishi & Sato, 1966 …”
Section: Discussionmentioning
confidence: 99%